Uji Efektivitas Ekstrak Tanaman Putri Malu (mimosa pudica linn) Sebagai Bahan Pengawet Alami Tomat - Fadlian, Fadlian; Hamzah, Baharuddin; Abram, Paulus Hengky (Jurnal Akademika Kimia, 2016)
Putri malu plant (mimosa pudica Linn) is known to contain saponin which is antibacterial compounds that can be used as a preservative. This study aims to prove whether the putri malu extracts can be used as a natural preservative for tomato and to determine the concentration of putri malu extracts to preserve tomatoes. The extraction method used was maceration and iodimetric titration to determine the levels of vitamin C before and after preservation. The results showed that the putri malu extract can be used as a natural preservative for tomatoes and the most effective concetration in preserving tomatoes was of 6%, that was for 11 days. At this level of concentration vitamin C showed the smallest value among others concentration where it decreased from 36.373 mg/100 g into 34.613 mg/100 g of material.